Experimental study of the effect of ClO2 on coal: Implication for coalbed methane recovery with oxidant stimulation. (15th May 2023) - Dang, Zheng; Su, Linan; Wang, Xiaoming; Hou, Shihui
Abstract: Oxidation stimulation is a potential method to improve coalbed methane (CBM) recovery. Three different rank coals were treated with ClO2 to investigate the effect of ClO2 on molecular structure, pore structure and gas migration capacity, and the mechanism of ClO2 stimulation on CBM recovery was analyzed. The results show that the contents of aromatic CC and aromatic C–H decrease, while those of polar oxygen functional groups increase. The change in pore structure mainly includes the increasing macropore volume and the decreasing micropore specific surface area and mesopore fractal dimension. The desorption, diffusion and seepage capacities of coal are improved. The enhancement ranges of maximum equivalent desorption rate and permeability are 1.74%–26.19% and 20%–80%, respectively, and the reduction range of tortuosity is 22.73–80.11%. Furthermore, the capillary pressure of coal is reduced, which means less water block damage in gas migration. Based on the analysis of the relationship between pore/macromolecular structure and gas migration capacity, a model of ClO2 stimulation for enhanced CBM recovery is established, and high-volatile bituminous coal is most conducive for ClO2 stimulation. Highlights: Aromatic ring decreases but oxygen functional group increases after ClO2 oxidation. Pore connectivity is improved but adsorption site of methane decreases. Desorption, diffusion and seepage capacities are improved. Water block damage is reduced. High-volatile bituminous coal is most conducive for ClO2 stimulation.